'Talking down monetary policy' – a note. Issue 20 (28th November 2017) - Tillmann, Peter
ABSTRACT: There is a recent debate about whether ultra-expansionary monetary policy is no longer effective in stimulating demand, a concern often voiced in the euro area in light of persistently low and even negative inflation. As a response, the European Central Bank (ECB) warns against 'talking down monetary policy' (ECB Vice-President Vítor Constâncio, 2016). This note uses a textbook model of optimal monetary policy to study a situation in which the public misperceives the interest rate elasticity of aggregate demand, which reflects policy effectiveness. We show that as a result of underestimating policy effectiveness demand shocks can no longer be stabilized perfectly, thus resulting in inefficient inflation and output dynamics. In the presence of misperceptions, a negative demand shock leads to a prolonged period of negative inflation rates.